Enseigner l'évolution et la nature des sciences face aux contestations d'élèves : essai de modélisation des postures enseignantes - Benoit Urgelli; Kenza Guelladress; Anne Quentin (Recherches en Éducation)
Teaching evolution is a socioscientific issue insofar as it can generate students’ challenges in the science class. It questions the place of beliefs about the origin of man, in secular school. During the year 2016, we have conducted an exploratory survey by online questionnaire for 53 science teachers. By multi-category analysis, the aim was to modelize the diversity of teachers' postures when students confused and amalgamed scholarly knowledge and religious beliefs. Most teachers state that this situation is infrequent. Some explains to the students the nature of sciences in relation to the nature of religions and beliefs (posture of understanding), others argue against religion by critical rationalism (posture of rebuttal). Some teachers say that exposing school audiences to scientific knowledge are sufficient to distance automatically their beliefs about the origin of man, without explaining the nature of science and religion (posture of avoidance). We will discuss the complexity of these postures, their hypothetical foundations, and an idea commonly admitted that teaching the nature of science and evolution should decrease the vivacity of this socioscientific issue.